Creating a capture zone in microfluidic flow greatly enhances the throughput and efficiency of cancer detection. (March 2019) - Sun, Mingrui; Xu, Jiangsheng; Shamul, James G.; Lu, Xiongbin; Husain, Syed; He, Xiaoming
Abstract: Efficient capture of rare circulating tumor cells (CTCs) from blood samples is valuable for early cancer detection to improve the management of cancer. In this work, we developed a highly efficient microfluidics-based method for detecting CTCs in human blood. This is achieved by creating separate capture and flow zones in the microfluidic device (ZonesChip) and using patterned dielectrophoretic force to direct cells from the flow zone into the capture zone. This separation of the capture and flow zones minimizes the negative impact of high flow speed (and thus high throughput) and force in the flow zone on the capture efficiency, overcoming a major bottleneck of contemporary microfluidic approaches using overlapping flow and capture zones for CTC detection. When the flow speed is high (≥0.58 mm/s) in the flow zone, the separation of capture and flow zones in our ZonesChip could improve the capture efficiency from ∼0% (for conventional device without separating the two zones) to ∼100%. Our ZonesChip shows great promise as an effective platform for the detection of CTCs in blood from patients with early/localized-stage colorectal tumors.